2014
DOI: 10.1371/journal.pone.0115015
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of COL4A3/COL4A4 Mutations amongst Families Segregating Glomerular Microscopic Hematuria and Evidence for Activation of the Unfolded Protein Response. Focal and Segmental Glomerulosclerosis Is a Frequent Development during Ageing

Abstract: Familial glomerular hematuria(s) comprise a genetically heterogeneous group of conditions which include Alport Syndrome (AS) and thin basement membrane nephropathy (TBMN). Here we investigated 57 Greek-Cypriot families presenting glomerular microscopic hematuria (GMH), with or without proteinuria or chronic kidney function decline, but excluded classical AS. We specifically searched the COL4A3/A4 genes and identified 8 heterozygous mutations in 16 families (28,1%). Eight non-related families featured the found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 55 publications
3
54
2
1
Order By: Relevance
“…Notwithstanding the likelihood that few patients may carry a non-detected mutation (large deletion or insertion), this result supports the fact that true heterozygosity for COL4A3/A4 mutations predisposes to chronic renal failure (CRF)/ESRD, most probably through a mechanism that involves FSGS development [30]. In recognition of these findings, the third edition of the United Kingdom guidelines for Living Donor Kidney Transplantation included a special clause recommending that ‘referral to a geneticist is mandatory in potential donors of Cypriot origin, where associations of TBMN and FSGS leading to significant rates of renal failure have been noted' (http://www.bts.org.uk/Documents/Guidelines/Active/UK%20Guidelines%20for%20Living%20Donor%20Kidney%20July%202011.pdf).…”
Section: Tbmn and Accompanied Fsgs In The Molecular Genetics Eramentioning
confidence: 67%
See 1 more Smart Citation
“…Notwithstanding the likelihood that few patients may carry a non-detected mutation (large deletion or insertion), this result supports the fact that true heterozygosity for COL4A3/A4 mutations predisposes to chronic renal failure (CRF)/ESRD, most probably through a mechanism that involves FSGS development [30]. In recognition of these findings, the third edition of the United Kingdom guidelines for Living Donor Kidney Transplantation included a special clause recommending that ‘referral to a geneticist is mandatory in potential donors of Cypriot origin, where associations of TBMN and FSGS leading to significant rates of renal failure have been noted' (http://www.bts.org.uk/Documents/Guidelines/Active/UK%20Guidelines%20for%20Living%20Donor%20Kidney%20July%202011.pdf).…”
Section: Tbmn and Accompanied Fsgs In The Molecular Genetics Eramentioning
confidence: 67%
“…In the same cohort, there were 26 biopsies available from patients in 17 families. In all the 26 biopsies, FSGS was a prominent histological finding [12,30]. …”
Section: Tbmn and Accompanied Fsgs In The Molecular Genetics Eramentioning
confidence: 99%
“…Although most affected individuals develop hematuria in childhood, proteinuria, renal failure, and extrarenal disorders are not observed in patients with TBMN, and the molecular mechanisms responsible for the different clinical courses of ADAS and TBMN remain unclear. Recent studies have revealed correlations between FSGS and heterozygous mutations in COL4A3 or COL4A4 (3,4), and 10% of patients diagnosed with familial FSGS showed heterozygous mutations in these two genes (5). A recent study using next generation sequencing (NGS) analysis revealed high proportions of mutations in COL4A3 and COL4A4 and a higher incidence of ADAS than previously reported (6).…”
Section: Introductionmentioning
confidence: 97%
“…ARAS occurs in about 15% of patients as a result of homozygous or compound heterozygous mutations in the COL4A3 or COL4A4 gene, whereas ADAS occurs in ,5% of patients and arises as a result of heterozygous mutations in the COL4A3 and/or COL4A4 gene encoding the type 4 collagen a3-or a4-chain, respectively (2). However, heterozygous mutations in COL4A3 or COL4A4 are also found in about 40% of patients with thin basement membrane nephropathy (TBMN) (3). Although most affected individuals develop hematuria in childhood, proteinuria, renal failure, and extrarenal disorders are not observed in patients with TBMN, and the molecular mechanisms responsible for the different clinical courses of ADAS and TBMN remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of TBMN and FSGS are not entirely clear. It is reported that TBMN, characterized by persistent glomerular hematuria, minimal proteinuria and normal renal function, is caused by heterozygous mutations in the COL4A3 or COL4A4 genes in about 40% of the patients [Papazachariou et al, 2014]. As a pathological phenotype, the causative genes of FSGS have been consistently investigated [Barua et al, 2014;Huynh Cong et al, 2014].…”
mentioning
confidence: 99%